2021
DOI: 10.1002/fsn3.2520
|View full text |Cite
|
Sign up to set email alerts
|

A proposed lectin‐mediated mechanism to explain the in Vivo antihyperglycemic activity of γ‐conglutin from Lupinus albus seeds

Abstract: Goldstein et al. (1980) defined lectin as a "protein or glycoprotein of non-immune origin (thus excluding immunoglobulins) which bind in a stable manner (thus excluding enzymes and carbohydrate sensor/ transport proteins) to carbohydrates." Plant lectins exert a vast panel of bioactivities (Ribeiro et al., 2018. Lupinus albus is a legume whose seeds contain reserve proteins exhibiting an array of bioactivities as wide as insecticide, fungicide (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The serum levels of creatinine and urea in all treated groups presented lower levels than in the control group. However, these lower results were not interpreted as an indication of toxicity since the control group (which received only water) also showed lower values compared to historical control values (0.28–0.37 mg/dL) [ 28 , 29 ]. The observation of decreased values of creatinine led us to discard the presence of toxicity since only increased creatinine levels are considered indicative of kidney injury [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The serum levels of creatinine and urea in all treated groups presented lower levels than in the control group. However, these lower results were not interpreted as an indication of toxicity since the control group (which received only water) also showed lower values compared to historical control values (0.28–0.37 mg/dL) [ 28 , 29 ]. The observation of decreased values of creatinine led us to discard the presence of toxicity since only increased creatinine levels are considered indicative of kidney injury [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…The Ames test was carried out following OECD guideline No. 471 [ 24 ] and the ICH S2 (R1) guideline [ 29 ], according to previously published protocols [ 37 , 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…Only the protein from soy beverages, with the exception of low amounts of cysteine and methionine, was comparable to cow’s milk when nutritional composition and health benefits are discussed among commercial vegetable alternatives ( 50 ). Several advantages for human health are attributed to chickpea proteins and lupin proteins: the lupin lectin γ-conglutin, a globulin composed of 42 kDa subunits, showed beneficial properties through its reducing effect in glycemia being suitable for diabetics ( 14 , 51 ); the deflamin protein found in legume seeds, namely lupin and chickpea, has been shown to be anti-inflammatory in in vitro models with various colon cancer cell lines as well as in vivo models of acute and chronic disease, presenting inhibitory bioactivity against MMP-9 ( 24 , 27 ). Also, the seed reserve protein β-conglutin from Lupinus albus exerted action on glycemic modulation and reduced the circulating cholesterol ( 15 ), and a natural 210 kDa glyco-oligomer fungicide, termed Blad-containing oligomer present in Lupinus albus , showed potent antifungal activity against both human and phytopathogenic fungi ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…The technique used to remove offflavors from legume-based beverages is thermal inactivation, but high temperatures lead to denaturation, aggregation, reduction in protein solubility, and nutrient losses (e.g., vitamins and minerals), which have restricted its use as a promising technology. In addition, some bioactive compounds from legume seeds, such as protease inhibitors (PIs), seed reserve proteins (γ-conglutin), lectins, phytates, oligosaccharides, saponins, and phenolic compounds may have important metabolic effects on the consumer's health (11)(12)(13)(14)(15). Some of these substances are beneficial, while others are considered anti-nutritional factors, which overall impair digestion, such as PIs, which decrease the digestibility and absorption of proteins (16).…”
Section: Introductionmentioning
confidence: 99%
“…Duranti et al (1995) reported a L. albus -conglutin with lectin-like activity and the ability to bind glycoproteins. Recently, an hemagglutinating -conglutin from L. albus was isolated (Grácio et al, 2021), but its activity was not constant in different purified batches, indicating that the methodology was not ideal. The hemagglutinating activity (Schoeneberger et al, 1982;Djabayan-Djibeyan et al, 2022) and the affinity for galactose of seed extracts from Lupinus mutabilis was reported (Falcon, 2000b), but the purification protocols were not suitable and caused the loss of the hemagglutinating capacity (Falcón et al, 2000b).…”
Section: Introductionmentioning
confidence: 99%